(untitled) (Global Journal of Computer Science and Technology, 2021)
Abstract Blockchain is transaction process which minimize transaction and data items of data sets that are encrypted transferred data items with secure data It is peer to peer technology The Blockchain is transaction flow or series of transactions Blackboard technology is used transaction store and retrieve independently In This paper Blockchain and blackboard technology is combined for transaction processing The communication cost and retriall cost will be reduced using Blockchain and Blackboard technology